Políticas públicas e (re)organização do espaço rural: desafios da implementação do Programa de Aquisição de Alimentos e do Programa Nacional de Alimentação Escolar no Município de Amargosa/Ba - Cerqueira, Míryan Siomara de Almeida (2017)
The reorganization of rural space is a process triggered by the interaction of multiple agents, including the State, small farmers and formal organizations (associations and cooperatives). In this process, public policies assume a central role when they are constituted as State action that focuses directly on certain categories and may incite changes. In Brazil, the redirects in public policies for agriculture, especially since 2003, were responsible for promoting the creation of new forms of action or restructuring existing ones. In this year there was the creation of the Food Acquisition Program (PAA), and in 2009, with Law No. 11,947 / 2009, there is a modification in the National School Feeding Program (PNAE), by establishing to the states and counties the obligation to allocate , at least 30% of its resources for the purchase of foodstuffs of small farmers or their organizations. The actions of the programs begin to share the same purposes in seeking to guarantee the human right to food and to strengthen the small production through the direct purchases of their products. Hence, the objective of the research is to analyze the spatial reorganization of the rural properties of the cooperative from the implementation of the Food Acquisition Program and the National School Feeding Program in the municipality of Amargosa/BA. The research pointed out that the implementation of the PAA and the PNAE resulted in the consolidation of the partnership between the public authority and the Family Farming Cooperative and Solidarity Economy of the Jiquiriçá Valley (COOAMA), which raised important place of sale of the products. The actions of the programs propel the spatial reorganization of the properties by promoting important interventions in the systems of objects and in the systems of actions that condescend the production of the space. In addition, although the implementation presents some challenges, it has allowed the valorization of the small farmers, minimizes the action of the middlemen, the prices practiced are in line with the local reality and contributes to assure the Food and Nutritional Security of the individuals that are benefited with the acquired foods.